Religion, crime, and financial reporting - Christian Hofmann; Nina Schwaiger (Journal of Business Economics, 2020)
The literature provides evidence on the separate roles of injunctive and descriptive norms in explaining corporate financial reporting, ignoring that descriptive norms are likely endogenous and partly explained by injunctive norms. We jointly analyze the direct and indirect effects of religious social norms (an injunctive norm) via local crime rates (a descriptive norm) on financial reporting quality. We find that religious social norms relate negatively to corporate earnings management and tax avoidance. We also show that this association is partially explained by crime rates in the firm's geographical environment, underlining the indirect relation between religious social norms and financial reporting quality. Overall, the study highlights the importance of considering the interrelations between injunctive and descriptive norms when analyzing the effect of norms on corporate decision-making.
Keywords: D22; M14; M40; 650; Injunctive norms; Religion; Descriptive norms; Crime; Earnings management; Tax avoidance